Kritik dan Implementasi Kapitalisme dalam Pendidikan Kontemporer : Kajian terhadap Komersialisasi Institusi Pendidikan Tinggi di Indonesia - Nadzifah A’isyah Fauzi; Zalfa Zayyana; Harits Mafaza; Abdul Khobir (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Higher education in Indonesia has undergone significant transformation due to the implementation of a capitalist system that emphasizes profit orientation and business logic. The commercialization of educational institutions has resulted in limited access, particularly for low- and middle-income communities, and has led to social inequality and a shift in the educational paradigm toward commodification. This study uses qualitative methods with literature review to examine the impact of capitalism and commercialization in higher education. The findings reveal an increase in tuition fees, the commodification of knowledge, and the privatization of universities, which reduce access and lower the quality of education. Criticism of educational capitalism emphasizes the importance of social and spiritual values and equal access. Therefore, it is recommended that policy reforms balance the roles of the state and the private sector, strengthen regulations, and expand access to fair and quality education for the sake of higher education that is oriented towards social welfare and sustainability.